PENYULUHAN HUKUM PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DI KEL. PURWOSARI, KEC. LAWEYAN, KOTA SURAKARTA - Irpan, YB; Susilowati, Endang Yuliana; Sekartaji, Cindi; Rahman, Zulfi (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Forms of domestic violence action in the community Kel. Purwosari, Kec. Laweyan, the city of Surakarta still does not need to be reported by the surrounding community. This is because there is a reason that acts of domestic violence are internal family matters and other people do not need to interfere to then be able to intervene or even report these acts of domestic violence. From the above conditions, it can be seen that not many people know that anyone can report this action to anyone who knows about the incident. This is a mandate from the existence of Law no. 23 of 2004 concerning the Elimination of Domestic Violence. Meanwhile, if you look at the conditions in the community, it turns out that domestic violence is taboo for others to know and it is a shame for the head of the family that he is considered unable to take care of his household affairs properly until he has to commit domestic violence to his family members. In addition, there are also Kelurahan officials who do not know that this is also a collective responsibility in order to minimize the increase in cases of domestic violence in Indonesia. Where this usually leads to divorce in marriage and the psychology of children from victims of domestic violence.